Exploring Stakeholder and Parent Perspectives of a County Response to Adolescent Vaping and E-Cigarette Use - Kurji, Natasha (Journal of drug issues, 2021)
In the United States, regular cigarette use has steadily declined over the years; however, it has been met with an increase in vaping and e-cigarette use. In Tampa, Florida, this trend has been found especially prevalent among school-aged youth. To combat issues of substance use among youth and prevent criminalization for nonviolent crimes, school-age youth cited for use and possession of tobacco products in Hillsborough County were mandated to attend the Youth Tobacco Awareness Course (YTAC). The aim of this study was to investigate YTAC for its perceived effectiveness and usefulness in mitigating adolescent e-cigarette use. Classroom observations, parent focus groups, and program stakeholder interviews were conducted to comprehensively evaluate this program. Findings from this evaluation led to a deeper understanding of the barriers and facilitators to an effective course, the needs and perceptions of program stakeholders, as well as recommendations for improved future interventions.